God Emperor of Dune - Herbert, Frank (New York : Putnam, 2019)
Fourth book in the Dune series. Takes place 3500 years after the events of the original trilogy. Tells the story of Leto, the son of Paul Atreides, who has traded his humanity to become an immortal sandworm of Dune.
School Library Journal
Wilson's Fiction
Wilson's Senior High School
Young Adult
Keywords: Dune (Imaginary place) -- Fiction; Science fiction